2006
DOI: 10.1038/sj.ki.5000147
|View full text |Cite
|
Sign up to set email alerts
|

A coding polymorphism in the 12-lipoxygenase gene is associated to essential hypertension and urinary 12(S)-HETE

Abstract: The arachidonic acid-derived metabolite 12-(S)hydroxyeicosatetraenoic acid (12(S)-HETE), catalyzed by 12-lipoxygenase (12-LOX, ALOX12), exhibits a variety of biological activities with implications in cardiovascular disease. Previous studies have shown higher urinary excretion of this metabolite in essential hypertension. The aim of this study was to analyze the association of polymorphisms in ALOX12 with hypertension and urinary levels of 12(S)-HETE. We studied 200 patients with essential hypertension (aged 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 24 publications
(32 reference statements)
1
22
1
Order By: Relevance
“…as shown in table ii, the frequencies of the variants identified in the Indian population (present study) were compared to the frequencies reported in caucasians (42,43), Blacks (42), chinese (40), Koreans (44), Brazilians (45) and Spanish (27). the frequencies appeared to vary in the various populations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…as shown in table ii, the frequencies of the variants identified in the Indian population (present study) were compared to the frequencies reported in caucasians (42,43), Blacks (42), chinese (40), Koreans (44), Brazilians (45) and Spanish (27). the frequencies appeared to vary in the various populations.…”
Section: Resultsmentioning
confidence: 99%
“…One recent publication also reported the association of alOx12 with the onset of natural menopause in caucasian females (54), indicating a role for alOx12 in hormone-related events in females. the alOx12 polymorphism has been shown to be associated with diseases, including hypertension, diabetic nephropathy and colorectal cancer (27). however, little information exists on the association of the alOx12 polymorphism with other types of cancers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study of 200 patients with essential hypertension (aged 56  1 years, mean  s.e.m., including 97 males) and 166 matched controls (aged 54  1 years, 91 males), Quintana et al, [42] found that a non-synonymous polymorphism in ALOX12 is associated with both essential hypertension and urinary levels of 12(S)-HETE.…”
Section: Chromosome 10mentioning
confidence: 99%